Secukinumab-induced Raynaud's phenomenon: first report in the literature - Senol Kobak (SAGE Publishing, 2020)
Secukinumab is an IL-17A antagonist that has proven efficacy in the treatment of patients with ankylosing spondylitis (AS) and psoriatic arthritis. Side effects of the drug include infections, skin rashes, and allergic reactions. Raynaud's phenomenon (RP), a vasospastic syndrome and an important feature of different connective tissue diseases, is not an expected finding in AS patients. This article reports the development of secukinumab-related RP in a 35-year-old female patient with AS. Treatment with secukinumab was continued and RP was treated with low-dose aspirin and a calcium-channel blocker.